Hukum dan Etika dalam Perjanjian Lama: Panduan untuk Kehidupan Sehari-hari Menurut Mikha 6:8 - Vera Agustin; Eka Nurlatu; Malik Bambangan (STIKAS Santo Yohanes Salib Kalimantan Barat, 2025)
This article explores the law and ethics of the Old Testament, drawing on Micah 6:8; highlighting its relevance as a guide for everyday life. In the often complex and conflicted modern context, the principles contained in these ancient texts offer profound insights into how to live meaningful and ethical lives. The Torah, consisting of commandments and regulations, served not only as a religious guide for the Israelites, but also as a moral foundation that can be applied by anyone seeking justice, love, and integrity in social interactions. This article examines various aspects of the law, including social justice, protection of the weak, and individual responsibility to the community. In addition, the ethics of the Old Testament emphasize the importance of the relationship between humans and God, as well as between humans. Values ​​such as compassion, forgiveness, and respect are at the heart of these teachings, encouraging individuals to live in harmony with themselves and others. Through in-depth analysis, this article also provides concrete examples of how these principles can be applied in everyday life, whether in personal, social, or professional contexts. In this way, readers are expected to find inspiration and practical guidance for living a more ethical and meaningful life, in line with teachings that have existed for thousands of years.